2004
DOI: 10.1088/0967-3334/25/5/r01
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid dynamics

Abstract: Hydrocephalus is far more complicated than a simple disorder of CSF circulation. Historically, it has been diagnosed using clinical and psychomotor assessment plus brain imaging. The role of physiological measurement to aid diagnosis becomes more appreciated in current clinical practice. This has been reflected by recently formulated guidelines for the management of normal pressure hydrocephalus. Clinical measurement in hydrocephalus is mainly related to intracranial pressure (ICP) and cerebral blood flow. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 91 publications
3
141
0
Order By: Relevance
“…A second set of experiments using blank culture inserts with both SFM and media with 10 per cent serum showed that the culture inserts with SFM represented a negligible source of resistance when compared with the cellular layer. This linear relationship is consistent with numerous previous studies in both animals and humans (Welch & Pollay 1961;Ekstedt 1978;Czosnyka et al 2004;Lenfeldt et al 2007;Andersson et al 2008). Further characterization of human permeability values under pathological conditions such as increased pressure and with increased loads of cytotoxic proteins is needed.…”
supporting
confidence: 90%
“…A second set of experiments using blank culture inserts with both SFM and media with 10 per cent serum showed that the culture inserts with SFM represented a negligible source of resistance when compared with the cellular layer. This linear relationship is consistent with numerous previous studies in both animals and humans (Welch & Pollay 1961;Ekstedt 1978;Czosnyka et al 2004;Lenfeldt et al 2007;Andersson et al 2008). Further characterization of human permeability values under pathological conditions such as increased pressure and with increased loads of cytotoxic proteins is needed.…”
supporting
confidence: 90%
“…Besides, it has been suggested that volume load during ITs may also have a relevant impact in the compliance of the brain and cerebral blood vessels. This issue leads to an exhausted compensatory reserve in the plateau phase of ITs, independently of the pathogenesis of hydrocephalus [7,43]. In this study, we found a decrease in irregularity and variability, together with a higher degree of similarity in the spectral content of the ICP waveform in the plateau phase with respect to the basal phase.…”
Section: Respiratory and Pulse-driven Abnormalities In Nphsupporting
confidence: 46%
“…Despite the recent advances, treatment is sometimes based on a limited knowledge of the underlying pathophysiology [6]. Therefore, the study of intracranial pressure (ICP) and CSF dynamics can provide valuable information on the management of patients with hydrocephalus [7].…”
Section: Introductionmentioning
confidence: 99%
“…The CSF dynamic model is not valid at low ICP levels [11,31], which will affect the infusion test analysis for patients where data is collected below this pressure. In this study the infusion phase was started at an ICP outside the model range in one patient (see figure 2).…”
Section: Limitations Of the Csf Dynamic Modelmentioning
confidence: 99%
“…[11,18,25]. It is a lumped model, and thus the sites of secretion and absorption are not specifically modelled.…”
Section: Assumptions Of the Csf Dynamic Modelmentioning
confidence: 99%